THE HAIRBALL IN THE ADVENTURES OF HUCKLEBERRY FINN: A MARXIST ANALYSIS - Putri, Vincentia Aprilla (Universitas Muhammadiyah Lampung, 2025)
This study examines the symbolism of the hairball in Mark Twain's Adventures of Huckleberry Finn through a Marxist lens, revealing its significance as a reflection of class struggle and power dynamics. The analysis is done qualitatively and it demonstrates how the hairball embodies materialism, exemplifies false consciousness, and reinforces the imbalance of power between the bourgeoisie and the proletariat in the novel. By requiring payment for its fortune-telling services, the hairball highlights the pervasiveness of capitalist values. Furthermore, the study connects the hairball's symbolism to contemporary issues which highlight the novel's enduring relevance in understanding economic inequality and exploitation. This analysis shows that The Adventures of Huckleberry Finn serves as a critique of the social world and reflects situations that continue to be relevant today.